2024
DOI: 10.1038/s41586-024-07379-z
|View full text |Cite|
|
Sign up to set email alerts
|

Tumour-selective activity of RAS-GTP inhibition in pancreatic cancer

Urszula N. Wasko,
Jingjing Jiang,
Tanner C. Dalton
et al.

Abstract: Broad-spectrum RAS inhibition has the potential to benefit roughly a quarter of human patients with cancer whose tumours are driven by RAS mutations1,2. RMC-7977 is a highly selective inhibitor of the active GTP-bound forms of KRAS, HRAS and NRAS, with affinity for both mutant and wild-type variants3. More than 90% of cases of human pancreatic ductal adenocarcinoma (PDAC) are driven by activating mutations in KRAS4. Here we assessed the therapeutic potential of RMC-7977 in a comprehensive range of PDAC models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Adaptive K-Ras inhibitor resistance is accompanied by significant metabolic reprogramming of cancer cells, including hyperactivation of the PI3K/AKT pathway 17,18 , elevated TCA cycle flux 19 , Myc amplification 20 , and upregulation of mitochondrial biogenesis 21 , culminating in heightened reliance on oxidative phosphorylation (OXPHOS). 21,22 As K-Ras pathway inhibition impairs glycolysis, forcing cancer cells to rely on OXPHOS for their energetic demands, this mechanism of clinical resistance is expected to impact the entire pharmacological class and is already being reported in laboratory studies of other K-Ras mutant targeting drug candidates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive K-Ras inhibitor resistance is accompanied by significant metabolic reprogramming of cancer cells, including hyperactivation of the PI3K/AKT pathway 17,18 , elevated TCA cycle flux 19 , Myc amplification 20 , and upregulation of mitochondrial biogenesis 21 , culminating in heightened reliance on oxidative phosphorylation (OXPHOS). 21,22 As K-Ras pathway inhibition impairs glycolysis, forcing cancer cells to rely on OXPHOS for their energetic demands, this mechanism of clinical resistance is expected to impact the entire pharmacological class and is already being reported in laboratory studies of other K-Ras mutant targeting drug candidates.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that acquired resistance to the K-Ras G12D inhibitor MRTX1133 in human PDAC cells is associated with feedback activation of ERBB/AKT signaling and enhanced OXPHOS. 14 Resistance to the mechanistically orthogonal pan K-Ras(ON) inhibitor RM-7977 has been recently reported in murine models of PDAC, and is associated with Myc amplification 20 . While metabolic profiling was not performed in this study, Myc overexpression has been shown to result in increased mitochondrial biogenesis 23 , and over 200 OXPHOS genes are regulated by Myc.…”
Section: Introductionmentioning
confidence: 99%